Area-Specific Assessment of Stratum Corneum Hydration and Transepidermal Water Loss in Pediatric Patients With Atopic Dermatitis - Kwon, Bo Yeon; Kim, Dohyeong; Shim, Kyungmin; Nguyen, Cindy; Lee, Hee Chul; Kang, Daeshik; Kim, Hohyun; Seo, Sung Chul (Dermatology Research and Practice, 2025)
SCORring atopic dermatitis (SCORAD) is widely used to assess the severity of atopic eczema, but score systems based on the entire body may be limited in effective monitoring and intervention. It is crucial to monitor moisture levels in each affected body part, but empirical research is still lacking. The objective of this study was to analyze the levels of stratum corneum hydration (SCH) and transepidermal water loss (TEWL) in atopic dermatitis (AD) patients, focusing on the presence and location of atopic lesions at different body sites. The levels of TEWL and SCH were measured using the AF200 AquaFlux and the Corneometer, respectively, at 15 body sites. 98 children under the age of 10 were measured, including 83 AD patients and 15 in the control group. Patients were also assessed with SCORAD and for the presence of atopic lesions at each body site. 58.7% of AD patients had lesions in the antecubital fossa and popliteal fossa, with corresponding low SCH levels and high TEWL in the upper body. The differences in TEWL between the control group and AD patients were confirmed significant in the neck and antecubital fossa regions, while differences in SCH were identified in the face, antecubital fossa, and popliteal fossa regions. A higher TEWL was found among AD patients with atopic lesions in the face and ankle. This study suggests that continuous monitoring of SCH and TEWL levels at specific body sites can provide insights into identifying vulnerable body areas to AD and supplement the SCORAD system for more effective clinical intervention and prevention strategies.